A New Method for the Synthesis of N,N´ -Disubstituted Picolinic Amides - H. Hussein Badie , Salim; Ahmed Widad, A.; Al-Kattan, T.A.; Al-Rawi, Jasim M.A (Asian Journal of Chemistry, 2010)
Reaction of N-substituted pyrrolopyridine dione with appropriate amines had led to. the formation of a series of new N, N´-disubstituted picolinic amides in good yields. These products have been investigated by spectroscopic analyses.